Enhancing The Role of Arctic port States in Ensuring Maritime Safety and Combating Vessel-source Pollution in the Arctic Region. - Elserafy, Shadi (UiT Norges arktiske universitet, 2016)
The remoteness of the Arctic region, the harsh yet sensitive environment and the lack of infrastructure poses great challenges on Arctic States. Further, it highlighted the emerging need of a comprehensive regulatory framework to ensure that adequate vessel safety standards and environmental protections are in place. Port States can play a very important role in combating vessel-source pollution and ensuring maritime safety in the Arctic region. The thesis seeks to to examine whether the current international legal framework of the law of the sea, is sufficient to provide Arctic port States with effective legislative and executive powers to ensure maritime safety and the protection of the marine environment from vessels-source pollution. The thesis also aims to investigate several options for enhancing and strengthening Arctic port State jurisdiction. The first option is by effective implementation of Articles 211(3) and 218 of the LOSC. The Second is by developing a PSC strategy in the Arctic region. The third is by exercising port State residual jurisdiction.